2011
DOI: 10.1016/j.nuclphysa.2011.01.022
|View full text |Cite
|
Sign up to set email alerts
|

On the sensitivity of the energy of vanishing flow towards mass asymmetry of colliding nuclei

Abstract: We demonstrate the role of the mass asymmetry in the energy of vanishing flow by studying asymmetric reactions throughout the periodic table and over entire colliding geometry. Our results, which are almost independent of the system size and as well as of the colliding geometries indicate a sizable effect of the asymmetry of the reaction on the energy of vanishing flow.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…[14][15][16][17]. Recently, using the dynamic approach based on the macroscopic models, the isospin effects have been examined for 40 Ca+ 90,96 Zr, 48 Ca+ 90 Zr fusion reactions [18].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17]. Recently, using the dynamic approach based on the macroscopic models, the isospin effects have been examined for 40 Ca+ 90,96 Zr, 48 Ca+ 90 Zr fusion reactions [18].…”
Section: Introductionmentioning
confidence: 99%
“…The information about them in interactions of light and medium projectile nuclei with various target nuclei is very restricted. Recently there has been renewed interesting in asymmetric systems since they offer more complete information than symmetric ones [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zhang et al [2] reported the system mass dependence of E T rans at a fixed colliding geometry for the reactions of 58 Ni + 58 Ni, 90 Zr + 90 Zr, 124 S n + 124 S n, 160 Gd + 160 Gd, 197 Au + 197 Au and 112 S n + 112 S n. All these studies take only symmetric reactions into account. Efforts have been made theoretically to study the effect of mass asymmetry of a reaction on multifragmentation [3], transverse in-plane flow and its disappearance [4] and the transverse momentum dependence of elliptical flow [5]. V. Kaur et al [5] reported that for mass asymmetric systems, the transition energy increases with mass asymmetry.…”
Section: Introductionmentioning
confidence: 99%